An effective immunotherapy regimen for VGKC antibody-positive limbic encephalitis. Issue 10 (26th July 2010) - Wong, S H; Saunders, M D; Larner, A J; Das, K; Hart, I K
Abstract : Background: Voltage-gated potassium channel antibody-positive limbic encephalitis (VGKC+LE) frequently improves with immunotherapy, although the optimum regimen is unknown. The effectiveness of a combination immunomodulatory regimen was tested in consecutive VGKC+LE patients. Methods: This was an open-label prospective study of nine VGKC+LE patients. All patients had plasma exchange (50 ml/kg), intravenous immunoglobulin (2 g/kg) and intravenous methylprednisolone (1 g×3), followed by maintenance oral prednisolone (1 mg/kg/day). Mycophenolate (2 g/day) was used in the first three patients. Assessments included serial clinical, cognitive, brain MRI and VGKC antibody testing. Results: Within 1 week, seizures and hyponatraemia remitted in all affected patients. Cognitive function improved in all patients within 3 months. MRI appearances improved substantially within 9 months, with remission of inflammation in the majority of patients. All achieved immunological remission with normal VGKC antibody titres within 1–4 months. Major adverse events of therapy included one septicaemia and one thrombosis on plasma exchange and one death from sepsis after incidental bowel surgery. One patient remains in remission after 40 months of follow up, 26 months after being off all treatment. Conclusions: Our immunotherapy regimen was effective for the treatment of the clinical, cognitive and immunological features of VGKC+LE. Radiological improvement was seen in the majority. Pending randomised controlled trials, this regimen is proposed for the treatment of VGKC+LE.